REKONFIGURASI 26 KANAL IRIGASI MENGGUNAKAN METODE BINARY FIREFLY ALGORITHMS (BFA) - M Yunus; Markhaban Siswanto; Slamet Imam Wahyudi; Soedarsono Soedarsono; Nazariano Rahman Wahyudi; Machrus Ali (Jurnal Teknika)
Reconfiguration of irrigation water channels on agricultural land aims to meet the water needs of rice fields. In its use, irrigation water must be used optimally. An automatic irrigation system is needed to provide water to plants in the desired conditions. In the irrigation control system, a servo motor simulates the control system using the Matlab 2013b software programme. Control simulations applied to irrigation prototypes are used to increase efficiency and determine the amount of irrigation water needed to regulate irrigation water distribution according to needs. As a controller comparison, an artificial intelligence method is used for controller tuning based on Binary Firefly Algorithm (BFA). The farthest water discharge results can be reduced in the reconfiguration model using the BFA method. So reconfiguring the network with BFA can reduce water discharge losses by 43.4538% of the water discharge losses from before